Challenges faced by teachers in online teaching during the pandemic - Che Haron, Sueraya; Abdul Rashid, Khadijah Khalilah; Haron, Sabrina; Mamat, Arifin; Abdullah, Nurazzelena (International knowledge Sharing Platform ( IISTE ), 2021)
The COVID-19 pandemic in 2020 has caused a major transformation in the education system around the world. Due to the closure of schools and other learning institutions, the teaching and learning that were once face to face are now conducted online. Sudden change of education landscape has put educators and students in harrowing time. This paper reviews literature to find out the challenges faced by educators when teaching online. The results reveal that all educators around the world are facing intrinsic challenges, such as little or no knowledge, skills and experience in the implementation of online teaching, as well as extrinsic challenges such as students having no Internet access and coverage and own no proper gadgets. It is found out that the biggest challenge faced by most local educators as compared to their counterparts in some parts of the world is their lower level of readiness in facing the transition from teaching traditionally to online.